Overview of Maize Improvement in India - Yadav, O. P.; Karjagi, C. G.; Jat, S. L.; Dhillon, B. S. (Indian Farming, 2015)
Directorate of Maize Research (DMR) and AICMIP have been involved in the development and release of superior maize hybrids and production technologies year after year. Developing high yielding hybrids with in-built resistance to diseases and pests and abiotic stresses tolerance and inventing novel biologicals for pest management, precision input management and conservation agriculture technologies would lead to profitable and ecologically sustainable maize-based farming systems in future.